The Character of God's Faithfulness: A Response to N. T. Wright - Gaventa, Beverly Roberts (Journal for the study of Paul and his letters, 2014)
N. T. Wright's two-volume work, Paul and the Faithfulness of God, attempts to consolidate and expand Wright's understanding of the Apostle Paul in light of Wright's extensive reconstruction of Judaism and Jesus of Nazareth, the Messiah. In addition to providing a brief discussion of Wright's general argument, this review responds to three types of concerns: (1) "key texts in Romans" that are critical to Wright's reading, specifically Rom 2:17-3:3 and the role of Israel; Rom 4, Abraham, and the covenant; and Rom 9-11, God, and Israel; (2) "revealing silences" on underrepresented issues, such as grace, the epistemological shift that accompanies the gospel, and the shape of Paul's ecclesiology in relation to practical, "on the ground" issues; and (3) Wright's treatment of "apocalyptic and anti-Judaism," which he roughly equates. Finally, this review reflects on the length, tenor, and rhetoric of the book.